2021
DOI: 10.3389/fmars.2021.761095
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of the Phototrophic Dinoflagellate Biecheleriopsis adriatica Grown Under Optimal Temperature and Cold and Heat Stress

Abstract: Dinoflagellates are a major component of marine ecosystems, and very cold and hot water may affect their survival. Global warming has amplified the magnitude of water temperature fluctuations. To investigate the molecular responses of dinoflagellates to very cold and hot water, we compared the differentially expressed genes of the phototrophic dinoflagellate Biecheleriopsis adriatica grown under optimal temperature and cold and heat stress. The number of genes upregulated or downregulated between optimal tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 144 publications
(183 reference statements)
2
2
0
Order By: Relevance
“…Our multiple lines of omics data demonstrate a strong coordinated response, particularly under chronic heat stress, that reduces energy production and consumption via the reduction of photosynthesis, carbon fixation, and amino acid biosynthesis, resulting in a suppressed central metabolism and protein synthesis. These observations lend support to the results of earlier transcriptome studies of pelagic dinoflagellates 59, 60 .…”
Section: Discussionsupporting
confidence: 89%
“…Our multiple lines of omics data demonstrate a strong coordinated response, particularly under chronic heat stress, that reduces energy production and consumption via the reduction of photosynthesis, carbon fixation, and amino acid biosynthesis, resulting in a suppressed central metabolism and protein synthesis. These observations lend support to the results of earlier transcriptome studies of pelagic dinoflagellates 59, 60 .…”
Section: Discussionsupporting
confidence: 89%
“…Our multiple lines of omics data demonstrate a strong coordinated response, particularly under chronic heat stress, that reduces energy production and consumption via the reduction of photosynthesis, carbon fixation, and amino acid biosynthesis, resulting in a suppressed central metabolism and protein synthesis. These observations lend support to the results of earlier transcriptome studies of pelagic dinoflagellates [78,79].…”
Section: Discussionsupporting
confidence: 88%
“…WGBS was performed in the dinoflagellates S. kawagutii and S. minutum at different temperature conditions, and global cytosine methylation levels provided similar results across samples of the same species, indicating the minimal effect of thermal stress on global methylation levels [ 78 ]. However, through a transcriptomic approach, it was observed that in the dinoflagellate Biecheleriopsis adriatica under cold stress, the “methylation” category had the highest difference between up- and down-regulated genes in gene ontology analysis, suggesting that cold stress may affect DNA methylation and gene expression in this microalga [ 128 ].…”
Section: Dna Methylation In Algae Response To Abiotic Stressmentioning
confidence: 99%